Development of a scale for measuring orthosomnia: the Bergen Orthosomnia Scale (BOS) - Guldbrandsen, Bodil V.; Baron, Kelly; Vedaa, Øystein; Bjorvatn, Bjørn; Pallesen, Ståle (Frontiers in Sleep, 2025)
IntroductionThis study aimed to extend the knowledge about orthosomnia, that is, excessive preoccupation with sleep, by developing a scale for its assessment.MethodsIn Study 1, an initial item pool was presented to 34 sleep experts for assessment using the Delphi method. In Study 2, relevant items were administered to 994 survey respondents (mean age = 42 years, SD = 13.2) for exploratory and confirmatory factor analysis. Two factors were retained, reflecting “interference” and “rigidity,” each comprising six items. In Study 3, the scale was validated against multiple validated instruments reflecting sleep-related behaviors and perceptions, the five-factor personality traits, the dark triad personality traits, measures of obsessive-compulsive disorder (OCD) and health anxiety, as well as demographic variables, in a new sample (n = 473, mean age = 41 years, SD = 12.8).ResultsThe two-factor model demonstrated acceptable fit (root mean square of approximation = 0.07, comparative fit index = 0.96, Tucker–Lewis Index = 0.95) with Cronbach's alphas of 0.87 and 0.88, and 3-week test–retest reliability of 0.74 and 0.82, respectively. Both orthosomnia factors correlated positively with sleep effort, dysfunctional beliefs and attitudes about sleep, narcissism, perfectionism, OCD, and health anxiety. The interference factor correlated positively with insomnia, neuroticism, psychopathy, and Machiavellianism and negatively with conscientiousness. The rigidity factor correlated positively with conscientiousness.ConclusionThe new scale for assessing orthosomnia possesses good psychometric properties and provides clinicians and researchers with an instrument for further investigating this new sleep construct.